PENYELESAIAN SENGKETA BISNIS SYARIAH - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The fast development of Islamic economic system in Indonesia stimulates a number of sharia-based businesses. This writing discusses the settlement methods of shariabased business disputes through Islamic arbitration, mediation, and court trial process whereby the parties may choose to be tried under the jurisdiction of district court or Islamic court.